The cardiovascular effects of amodiaquine and structurally related antimalarials: An individual patient data meta-analysis - Chan, XHS; Haeusler, IL; Win, YN; Pike, J; Hanboonkunupakarn, B; Hanafiah, M; Lee, SJ; Djimdé, A; Fanello, CI; Kiechel, J-R; Lacerda, MVG; Ogutu, B; et al. (Public Library of Science, 2021)
Background Amodiaquine is a 4-aminoquinoline antimalarial similar to chloroquine that is used extensively for the treatment and prevention of malaria. Data on the cardiovascular effects of amodiaquine are scarce, although transient effects on cardiac electrophysiology (electrocardiographic QT interval prolongation and sinus bradycardia) have been observed. We conducted an individual patient data meta-analysis to characterise the cardiovascular effects of amodiaquine and thereby support development of risk minimisation measures to improve the safety of this important antimalarial.